USULAN SKENARIO PENGELOLAAN ORANGUTAN (PONGO PYGMAEUS) DI KORIDOR TAMAN NASIONAL BETUNG KERIHUN-DANAU SENTARUM - Zapariza, Rudi; Gusmayanti, Evi (JURNAL BORNEO AKCAYA, 2015)
Orangutan populations in corridor Betung Kerihun National Park (BKNP) - Danau Sentarum National Park (DSNP) has decreased each year due to habitat fragmentation, land conversion, population growth and not-integration of planning among stakeholders. The purpose of this research are: (1). Build dynamic models of orangutan management in Corridor BKNP-TNDS. (2). Formulating management scenarios orangutan in Corridor BKNP-TNDS. This research has using primary data from interviews and focus group discussions (FGD), whereas secondary data from the results of previous research, journals and other information. The method of research used geographic information systems (GIS) to see the forest cover, stakeholder analysis to find of interests and influence among stakeholders and dynamic system to analyze variables that affect orangutan habitat and population. The study produced three scenarios orangutan management in Corridor BKNP-DSNP based on habitat carrying capacity. The first scenario is forest cover remains and oil palm plantation area corridor is not opened, the second scenario is the forest and oil palm plantations implementing regulation PP No. 71 Year 2014 concerning the protection and management of peatland ecosystems. Third scenario is adds to the forest cover in BKNP and TNDS. The possible scenario is added at the forest cover in both area BKNP and DSNP to obtain the environmental carrying capacity of the habitat of orangutans. Research recommendations is importance building orangutan habitat corridors that are acceptable to all stakeholders